2019
DOI: 10.1002/mgg3.670
|View full text |Cite
|
Sign up to set email alerts
|

Two de novo GJA1 mutation in two sporadic patients with erythrokeratodermia variabilis et progressiva

Abstract: Background Erythrokeratodermia variabilis et progressiva (EKVP, OMIM 133200) is a rare hereditary disorder characterized by varies from transient, fast moving erythema to persistent brown hyperkeratotic plaques. Recently, mutations in the genes gap junction alpha 1 gene (GJA1), GJB3, and GJB4 have been reported to cause EKVP. Here, we report the identification of two de novo missense mutations in the GJA1 gene in two unrelated individuals with EKVP. Methods The patients and his family members were subjected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Investigations of the mechanism for EKVP involve Cx43-A44V and Cx43-E227D, which have been reported to result in hemichannel localization failure and subsequent Golgi accumulation [73]. Two new mutations have since been discovered and are attributable to EKVP as well, producing similar phenotypes in cases [74]. In PPKCA1, Cx43-G8V has been reported to increased hemichannel activity, resulting in increased basal levels of Ca 2+ and its permeability [75].…”
Section: Cx43 Hemichannelsmentioning
confidence: 99%
“…Investigations of the mechanism for EKVP involve Cx43-A44V and Cx43-E227D, which have been reported to result in hemichannel localization failure and subsequent Golgi accumulation [73]. Two new mutations have since been discovered and are attributable to EKVP as well, producing similar phenotypes in cases [74]. In PPKCA1, Cx43-G8V has been reported to increased hemichannel activity, resulting in increased basal levels of Ca 2+ and its permeability [75].…”
Section: Cx43 Hemichannelsmentioning
confidence: 99%
“…While these lesions are not life-threatening, they cause substantial morbidity due to pain and irritation. EKVP is genetically heterogenous with linkages to seven genes that include three connexin-encoding genes: GJB3 (Cx31) [ 9 , 10 , 11 , 12 , 13 ], GJB4 (Cx30.3) [ 4 , 14 , 15 , 16 ], and GJA1 (Cx43) [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two novel de novo autosomal dominant missense variants in GJA1 (p.P283L and p.T290N) were identified in two unrelated Chinese patients with EKVP [ 18 ]. In both cases, these variants were not detected in unaffected family members and 100 unrelated controls, and no variants were identified in GJB3 or GJB4 [ 18 ], although other genes linked to EKVP were not investigated [ 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these patients even have severely compromised Cx43 function as many Cx43 mutants are dominant to the functional status of co-expressed wild type Cx43 [ 47 , 48 ]. However, Cx43 pathologies can occasionally affect the skin as a set of patients have been identified that harbor GJA1 mutations and present with erythrokeratodermia variabilis et progressiva (EKVP) [ 49 , 50 , 51 ]. These patients suffer from transient erythematous patches and hyperkeratotic plaques [ 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Cx43 pathologies can occasionally affect the skin as a set of patients have been identified that harbor GJA1 mutations and present with erythrokeratodermia variabilis et progressiva (EKVP) [ 49 , 50 , 51 ]. These patients suffer from transient erythematous patches and hyperkeratotic plaques [ 49 , 50 , 51 ]. Subsequent studies have assigned hyperactive Cx43 hemichannels as the potential cause of this skin pathology [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%